Highly Structured Service Learning: Positive Impacts on the Teacher Candidates, Cooperating Teachers, and Fourth Graders - Wasserman, Ph.D., Kathleen B (International Journal of Research on Service-Learning in Teacher Education, 2010)
This research project explored the reciprocal benefits of adding an integrated service-learning component to a required reading/language arts methods course. The undergraduate teacher candidates were immersed in classrooms at an urban, underserved school with low student performance and expected to implement a 16-hour language arts unit developed and modeled by the professor. The unit was designed to teach the undergraduates best practices in teaching comprehension and composition of expository text while simultaneously increasing the reading and writing skills of fourth grade students. Data were collected and analyzed from three constituencies: teacher candidates, cooperating teachers, and the fourth grade participants, using a qualitative approach. Findings verified that this program positively affected all populations.